2014
DOI: 10.1021/nl4039357
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-Intensity Magneto-Optical and Mechanical Effects in Metal Nanocolloids

Abstract: Magneto-plasmonics is a designation generally associated with ferromagnetic-plasmonic materials because such optical responses from nonmagnetic materials alone are considered weak. Here, we show that there exists a switching transition between linear and nonlinear magneto-optical behaviors in noble-metal nanocolloids that is observable at ultralow illumination intensities and direct current magnetic fields. The response is attributed to polarization-dependent nonzero-time-averaged plasmonic loops, vortex power… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Recently, composites using magnetic nanoparticles (MNPs) dispersed in organic matrices have offered an alternative low-cost method for generating MO materials [34][35][36][37][38][39]. Properly surface modified paramagnetic nanofillers, together with selected photomonomers, have resulting in thin film composites with good transparency [40,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, composites using magnetic nanoparticles (MNPs) dispersed in organic matrices have offered an alternative low-cost method for generating MO materials [34][35][36][37][38][39]. Properly surface modified paramagnetic nanofillers, together with selected photomonomers, have resulting in thin film composites with good transparency [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Various systems including MNPs and silica sol-gel porous matrix blends [36,37,[42][43][44], plasmonic enhanced shell MNPs [38,39,[45][46][47][48], and homopolymer stabilized core-shell MNP composites [34,35,[49][50][51] have been studied to understand both their scattering mechanisms and MO performance. Despite the high Verdet constants achieved in some of these composites, the resulting scattering from porous matrices produced by sol-gel methods [36,37,42] or aggregation of large NPs at higher concentrations [34,50] still limit the FR application of these materials at realistic length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled modeling and experimental efforts to develop 14 novel biosensing systems and therapeutic nanoplatforms based on core-shell geometries such as an iron oxide core with a gold shell and an iron-platinum core with a gold shell are underway. Moocarme et al 34 showed that there exists a switching transition between the linear and nonlinear magneto-optic behavior in noble-metal nanocolloids that is observable at ultralow illumination intensities and direct current magnetic fields. The response was attributed to polarization-dependent nonzero-time-averaged plasmonic loops, vortex power flows, and nanoparticle magnetization.…”
Section: Magneto-plasmonicsmentioning
confidence: 99%
“…where u i is the volume fraction of the ith type of magnetic particles, and l i and g i are defined by Eqs. (2), (5), and (6). The magnetic field inside the film is…”
Section: B Heat Production In a Nanocomposite Filmmentioning
confidence: 99%
“…The current understanding of interactions of nonmagnetic metal nanocomposites with the electromagnetic (EM) waves has been significantly advanced and enabled new exciting engineering applications mostly in the band of EM spectrum corresponding to the optical frequency range. [1][2][3][4][5][6][7][8][9] EM waves passing through a metal nanoparticle excite the oscillations of the charge carries, plasmons. Plasmon oscillations, in turn, change the properties of EM waves.…”
Section: Introductionmentioning
confidence: 99%